The Psychometric Properties of the French Version of the Trait Emotional Intelligence Questionnaire–Child Short Form. (June 2019) - Stassart, C.; Etienne, A.-M.; Luminet, O.; Kaïdi, I.; Lahaye, M.
The psychometric properties of the French version of the Trait Emotional Intelligence Questionnaire–Child Short Form (TEIQue-CSF) were investigated in a sample of 556 children 9 to 13 years of age. The internal consistency and temporal stability were satisfactory. A significant difference for gender, but not for age, was observed. With regard to the factor structure, the best fit was found for a two-factor solution, emotion control and socioemotionality. Regarding convergent validity, positive correlations were found with the total and all except one-factor scores of the Emotion Awareness Questionnaire score (EAQ30). Evidences of concurrent validity were demonstrated, with negative correlations with State-Trait Anxiety Inventory for Children (STAIC) and childhood anxiety sensitivity index (CASI). Results also showed a positive correlation with Children's Social Desirability Scale (CSD). In conclusion, these findings provide additional support for the use of the TEIQue-CSF for researchers and practitioners who want to assess emotion-related constructs in children.